Reactualisation of Stories of Women's Glory in the Qur'an as a Method of Husband and Wife Relationships in the Family - Alamsyah Alamsyah; M. Nurdin Zuhdi (Brajamusti Publication, 2024)
This article examines the stories of the glory of women in the Qur'an, with the method of human stories can take moral messages in it, because the fact is that until now the position of women is not only in the public sphere, in the domestic sphere (family) women still experience a lot of discrimination and injustice, women are often positioned as officers who play a role in the